Comparative Morphology and characterization of colletotrichum isolates occurring on Cocoa in Malaysia - Yee, M. F.; Meon, Sariah (Universiti Putra Malaysia Press, 1993)
Isolation from cocoa leaves showing symptoms of shot-hole, blight or irregular leaf spot and from cherelles and pod rot yielded Colletotrichum gloeosporioides. No distinct differences in cultural and morphological characteristics were noted between the various isolates. The fungus was found to grow and sporulate well at 3()C. Cocoa LeafExtract Agar (CllA) was the best medium for mycelial growth while Potato Dextrose Agar appeared to favour sporulation. Both cocoa leaves and injured pods were liable to infection by C. gloeosporioides. Three week old cocoa seedlings and cherelles were noted as the most susceptible stages.